Peningkatan Hasil Belajar Fisika Siswa Kelas XII MIPA 2 Melalui Penerapan Model Pembelajaran Discovery Learning Dengan Pendekatan Saintifik di SMA Negeri 8 Maros - Mutiara Siska Aprilia; Ariani Ariani; Rini Nurbayti; Farid Abdurrahman.A; Musdalifah Musdalifah; A.Novianti W; Sadrianto Sadrianto; Ririn Putri N (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Scientific approach enable student more active in course of learning to teach. Scientific approach enable student to learn at the same time hook;correlate with everyday life either in family environment, school and also masayarakat. Hence from that, with applying of expected by scientific approach of student more active because brought to be items to be hooked;correlated direct with real life. This research aim to to increase result of learning Physics XII MIPA class student 2 passing applying model study of Discovery learning with scientific approach 1. Mean score result of learning Physics student at I cycle is equal to 96,06 from ideal score which is possible reached by student namely 100 with deviasi standard 4,54. Becoming, can be said that by most XII MIPA class student 2 complete in study of cycle I. Applying model study of Discovery Learning with scientific approach can improve result learn Physics student at XII MIPA class 2. Applying model study of Discovery Learning with effective scientific approach can improve livelines frequency and activity in course of learning to teach as according to perception of student attitude during execution research of class action at I cycle and II cycle.